USING AMERICAN TV SHOWS TO IMPROVE ENGLISH LISTENING COMPREHENSION: A CASE STUDY AT AN ENGLISH CLASS = SỬ DỤNG CHƯƠNG TRÌNH TRUYỀN HÌNH MỸ ĐỂ CẢI THIỆN KHẢ NĂNG NGHE HIỂU: NGHIÊN CỨU Ở MỘT LỚP HỌC TIẾNG ANH - Phạm, Thị Ngọc Hà (2020)
As listening has gained recognition of being an important skill in language development, researchers are directing their interest towards teaching methodology and teaching materials in listening lessons. In accordance with the rising trend of using authentic materials in language, there comes up the question about effective methodology to exploit these materials. The purpose of this study was to investigate teaching methods and techniques to turn American TV shows into effective classroom materials to teach listening comprehension in an English class. It also aimed at examining students’ attitude toward their learing materials and the teacher’s teaching methods. The tertiary purpose of this research was to be able to make pedagogical recommendations to English teachers who wished to use authentic listening materials in their listening lessons. The first source of data for this qualitative study was participant observation and the secondary one was interviewing. Analysis of the collected data for the research question number one revealed that the teacher employed numerous methods in teaching listening, prominence of which were student need – centered, teacher-centered and “affective filter” hypothesis (Krashen, 1982). The process of screening American TV shows’ clips was painstaking and required the teacher’s investigation of students’ responses to each clip. Secondly, the analysis of interviews with students uncovered that the teacher’s teaching method and used listening materials were of students’ favour as they gave them fun and also motivation to self-improve their English competence. However, some classroom activities did not succeed in driving students’ learning motives. Finally, some recommedations were offered to vary the level of listening tasks, to increase the teacher’s attention to individuals to deal with their difficulties in comperehending fast-pace clips and unfarmiliar vocabulary, and to design an appropriate tool of measuring students’ listening comprehension development.